A CBCT study of changes in temporomandibular joint morphology with immediate implant placement and immediate loaded full-arch fixed dental prostheses - Rundong Zhang; Ziyu Ge; Xinrui Lang; Bo Qiao; Jiayi Chen; Baoding Ye; Yanzhen Zhang (BMC, 2024)
Abstract Background Dental implants are becoming a popular treatment of choice. Immediate implant placement with immediate loaded full-arch fixed dental prostheses (IPILFFDP) presents an attractive solution for edentulous and partially edentulous patients because of its high success rate, reduction in overall treatment time, and improved esthetics. However, whether it can minimize the risk of temporomandibular disorder (TMD) has not been previously studied. Objective To quantitatively evaluate the temporomandibular joint (TMJ) morphology changes before and after IPILFFDP, using cone beam computed tomography (CBCT). Methods Twelve participants without TMJ symptoms undergoing IPILFFDP were included in the study. Preoperative and 1-year postoperative assessment of CBCT scans were performed on 18 items related to TMJ and vertical dimensions. Mimics software was used for data analysis. T-test, Pearson, and Spearman correlation analyses were performed. Results There were no significant differences in bilateral joints between pre and post IPILFFDP. Compared with pre-treatment CBCT, post-treatment CBCT showed a significant increase in posterior joint space. There was an approximately 2 mm increase in the vertical dimension after IPILFFDP, which is correlated with an increase in the medial joint space. Conclusions For patients without TMJ-related signs and symptoms, the IPILFFDP could keep the neuromuscular memory of patient's facial muscles and occlusion, and use adapted centric posture as a guide, which led to more precise restoration of the original jaw position and may shed light in future related clinical studies.